ON WIJSMAN DEFERRED STATISTICAL CONVERGENCE OF DOUBLE SEQUENCES OF SETS - Yilmazer, Mehmet Cagri; Et, Mikail; Bhardwaj, Vinod K.; Gupta, Sandeep (Univ Nis, 2023)
In this article, we introduce the concepts of Wijsman deferred statistical convergence and Wijsman strong deferred Cesaro summability for double sequences of sets. Additionally, some properties and based results have been established under a few restrictions.
Keywords: statistical convergence; Cesaro summability; double sequences of sets